Review-A Comparative Evaluation of Redox Mediators for Li-O-2 Batteries: A Critical Review - Kwak, Won-Jin; Kim, Hun; Jung, Hun-Gi; Aurbach, Doron; Sun, Yang-Kook (ELECTROCHEMICAL SOC INC, 2018)
For resolving the low-energy efficiency issue of Li-O-2 batteries, many kinds of redox mediators (RMs) have been adapted. However, studies looking into the problems of RMs in these systems are insufficient. We compare herein effects and problems of RMs in Li-O-2 batteries by applying unique methodology, based on two types of cells, comparison between argon and oxygen atmospheres and combining electrochemistry in conjunction with spectroscopy. Using systematic electrochemical measurements, representative RMs in Li-O-2 battery prototypes were thoroughly explored with respect to oxygen presence, voltage ranges and scan rates. By this comparative, multi-parameters study we reached valuable insights. We identified possible routes for RMs degradation in Li-O-2 batteries related to the cathode side, using bi-compartments cells with solid electrolyte that blocks the crossover between the cathode and the Li metal sides. Based on comparative electrochemical and spectroscopic analyses, we confirmed that degradation of the RMs activity was caused by intrinsic decomposition of the RMs in the electrolyte solution at the cathode part, even before further reactions with reduced oxygen species. This work provides a realistic view of the role of important RMs in Li-oxygen cells and suggests guidelines for effective screening and selecting suitable RMs, mandatory components in Li-O-2 batteries. (C) The Author(s) 2018. Published by ECS.
Keywords: LITHIUM-OXYGEN BATTERIES; LI-AIR BATTERIES; SUPPRESSING CHARGING INSTABILITIES; EVOLUTION REACTIONS; LI2O2 OXIDATION; CARBON; ELECTROLYTE; STABILITY; REDUCTION; CATALYST